2022
DOI: 10.3389/fmicb.2022.830121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactic Acid Bacteria and Molasses Additives on Dynamic Fermentation Quality and Microbial Community of Native Grass Silage

Abstract: Ensiling native grass is an effective method to protect the nutritional quality of forage and alleviate feed shortages in the cold winter of the Inner Mongolian Plateau. To improve the usability of native grass resources as feed in China, the effects of lactic acid bacteria and molasses additions on the microbial population, fermentation quality, and nutritional quality of native grass during silage were investigated. Treatments were a control treatment with no additive (CK), lactic acid bacteria (L), molasses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 50 publications
9
28
0
1
Order By: Relevance
“…As expected, we found that the main organic acid content (LA, AA) in silage was negatively correlated with fermentation and chemical heterotrophic characteristics, while the pH was positively correlated. In addition, as determined in previously published studies ( Li P. et al, 2022 ; Li Y. et al, 2022 ), AN/TN was negatively related for fermentation and chemoheterotrophy, whereas it was positively related for nitrogen respiration, nitrite respiration and nitrite ammonification, which indicates that protein degradation was inhibited and more proteins were retained. This can also be confirmed by the positive correlation of CP with nitrogen respiration, nitrite respiration and nitrite ammonification.…”
Section: Resultssupporting
confidence: 66%
“…As expected, we found that the main organic acid content (LA, AA) in silage was negatively correlated with fermentation and chemical heterotrophic characteristics, while the pH was positively correlated. In addition, as determined in previously published studies ( Li P. et al, 2022 ; Li Y. et al, 2022 ), AN/TN was negatively related for fermentation and chemoheterotrophy, whereas it was positively related for nitrogen respiration, nitrite respiration and nitrite ammonification, which indicates that protein degradation was inhibited and more proteins were retained. This can also be confirmed by the positive correlation of CP with nitrogen respiration, nitrite respiration and nitrite ammonification.…”
Section: Resultssupporting
confidence: 66%
“…The changes in the fungal community structure were also explored, these results illustrated that the three groups distinctly separated from different time point, as reflected by the clustering of the samples by storage period using PCoA. Macroscopically, the storage period drove a separation in the fungal community (Figure 2D), the distinguishable changes among the three groups, following the reports that noticeable separation of the fungal community structure was observed in silage and hay during the various storage periods [3,20,21]. Various treatments and storage of hay favor different fungal contaminants and the storage period is the key factor in determining microbial community structure may be the main reason [3].…”
Section: Discussionsupporting
confidence: 62%
“…The common and unique OTUs was used to construct the Venn diagram by R (version 1.6.2). The alpha diversity for these samples were used the Chao1 value and Shannon index to evaluate richness and diversity [17][18][19][20], and Good's coverage were calculated through QIIME software. Principal coordinates analysis (PCoA) was conducted on OTU level by R (version 3.3.1) software based on weighted UniFrac distances.…”
Section: Bioinformatics and Statistical Analysismentioning
confidence: 99%
“…The primer pairs 27F and 1,492 R, which span the full length of the bacterial 16 S rRNA gene, were amplified using an ABI GeneAmp 9700 PCR thermocycler (ABI, CA, United States). The PCR amplification was performed following the methods of Li et al (2022) .…”
Section: Methodsmentioning
confidence: 99%